“O que Estamos A Fazer?” Ensaio Sobre a Economia Política da Promessa do Novo Imaginário Biomédico - Costa, José Carlos Pinto da (Trabalhos de Antropologia e Etnologia, 2020)
Sheila Jasanoff identified three key issues that could interfere with the co-production of futures in the context of the political economy of promise: the predominance of private organizations in the articulation and propagation of the imaginary; the existence of tensions over the definition of desirable futures; and the quality of the imaginary as translators of a society's understanding about good and evil. This essay reflects on the implications of the political economy of the promise of the new biomedicine in the production of the imagined futures by analysing these three issues through a cosmopolitical approach, following Isabelle Stengers' famous proposal, that is, starting from the question: “what are we busy doing?”.